(untitled) (Journal of Atomic and Molecular Sciences, 2010)
The singly (1s,ns)^3S^e, (1s,np)^3P^o, (1s,nd)^3D^e excited states and the doubly _2(1,0)_n^+1S^e and _2(1,0)_n^-3S^e (n≤10) autoionizing states of the helium isoelectronic sequence are investigated using Modified Atomic Orbital Theory (MAOT). Total energies up to Z = 10 and excitation energies with Z = 2 5 are presented and comparison with experimental and theoretical available results indicates a good agreement. In addition, the method is applied in the calculation of accurate results in very high Z - He isoelectronic sequence with 11≤ Z≤58 and with Z = 60, 70, 80, 90 and 92 for the (1s,ns)^1,3S^e, (1s,np)^1,3P^o, (1s,nd)^1,3D^e, _2(1,0)_n^+1S^e and _2(1,0)_n^-3S^e (n≤7) excited states. The results obtained for these high Z - He isoelectronic sequence are in good agreement with double sums over the complete hydrogen spectrum calculations Ivanov and Safronova.